Discoid Lupus Erythematosus of the Scalp in a Patient with Systemic Lupus Erythematosus: A Case Report with Complete Hair Regrowth - Garbelini-Lima,Cleide (2021)
ABSTRACT Scalp involvement with hair loss is common in systemic lupus erythematosus. Discoid lupus erythematosus may cause scarring alopecia, characterized by well-delimited erythematous plaques with scales, follicular hyperkeratosis and atrophy, which is considered a trichological emergency. Early diagnosis and treatment are necessary in order to prevent permanent hair loss. We describe a 44 years’ old female patient with systemic lupus erythematosus for 4 years, with multiple areas of occipitoparietal alopecia, erythematous plaques, atrophy, scales and some bloody crusts. Trichoscopy, histopathology and direct immunofluorescence led to the diagnosis of discoid lupus erythematosus. After 9 months treatment with thalidomide there was complete hair regrowth.